The effect of etched 3D printed Cu-bearing titanium alloy on the polarization of macrophage - Yan, Jinge; Huang, Wanyi; Kuang, Hai; Wang, Qiang; Li, Bo (Frontiers in Materials, 2022)
3D printed titanium alloys have been widely used as implants in orthopedic surgery and dentistry. In recent years, Cu-bearing titanium alloys has shown great advantages in tissue engineering due to its excellent antibacterial activity and biological effect. In the present study, three alloys namely TC4 alloy, TC4-5Cu alloy and TC4-6Cu alloy were fabricated by selective laser melting (SLM) technology. Acid etching treatment was used to modify the surface of the above alloys. The effect of different etched alloys on the biological behavior of macrophages (RAW264.7) was studied comprehensively. Results showed that acid etching had no effect on hydrophilicity and could contribute to higher cell adhesion, higher polarization of macrophages and lower ROS level. Moreover, Cu-bearing titanium exhibited the better cell adhesion and macrophage polarization potential, and the lower ROS level. In summary, acid etching treatment provided a promising strategy to improve the biological properties of the Cu-bearing titanium alloys by SLM.